Peranan Kompos Kulit Kopi dan Pupuk Kandang Ayam terhadap Ketersediaan Hara N, P, K dan Pertumbuhan Tanaman Jagung (Zea mays L.) di Tanah Ultisol - Fadhlurrahman, Syarif Novel; Hayati, Rita; Riduansyah, Riduansyah (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2025)
Ultisols are marginal soils that are low in nutrients and organic matter. The low nutrient and organic matter content needs to be improved with an ameliorant in the form of coffee husk compost combined with chicken manure, which is widely available in the soil. This study aims to determine the effect of combining coffee skin compost and chicken manure on the availability of N, P, and K nutrients, as well as the growth of corn plants in ultisol soil. The research design used in this study was a completely randomized design (CRD) with a factorial arrangement, consisting of 9 treatments and 3 replications, resulting in 27 sample plots. The treatments included two factors: factor A (coffee skin compost) and factor P (chicken manure). The results showed that the chicken manure treatment increased soil pH, organic carbon, total nitrogen, available phosphorus, and exchangeable potassium, while the coffee skin compost treatment enhanced exchangeable potassium. However, neither treatment had a significant effect on plant height or stem diameter, and no significant interaction was observed between the two factors.